2016
DOI: 10.1002/nml.21229
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathways from Transformational Leadership to Job Satisfaction

Abstract: Transformational leaders are known to inspire and motivate their followers, thereby leading to enhanced job satisfaction. Job satisfaction is an intellectual concept regarding individuals' attitudes toward their jobs. This study asserts that the underlying mechanisms for transformational leadership to affect employee satisfaction are trust in the community, including the leader (that is, organization) and trust in the self, namely self-efficacy. Leadership is specifically associated with continual transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…The results suggest that the effect of transformational leadership on volunteers’ proactive behavior is partially mediated by role breadth self‐efficacy ( can do ) and positive affect ( energized to ). This is in line with previous research, which has shown the positive effect of transformational leaders on self‐efficacy (Yıldız & Şimşek, ), and positive emotions for volunteers (Rowold & Rohmann, ). These results integrate these findings in a comprehensive model that may partially explain conflicting findings in previous research (Dwyer et al, ) exploring only the direct effect of transformational leadership on volunteer contributions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results suggest that the effect of transformational leadership on volunteers’ proactive behavior is partially mediated by role breadth self‐efficacy ( can do ) and positive affect ( energized to ). This is in line with previous research, which has shown the positive effect of transformational leaders on self‐efficacy (Yıldız & Şimşek, ), and positive emotions for volunteers (Rowold & Rohmann, ). These results integrate these findings in a comprehensive model that may partially explain conflicting findings in previous research (Dwyer et al, ) exploring only the direct effect of transformational leadership on volunteer contributions.…”
Section: Discussionsupporting
confidence: 92%
“…The relevance of can do motivation to proactive behavior is through the impact of the belief that the proactive behavior will lead to the desired outcome (Frese & Fay, ), the perceived costs (Aspinwall, ), and the confidence of being able to engage in proactive behaviors, in other words, self‐efficacy (Ohly & Fritz, ; Parker & Collins, ). Previous research found the relation between transformational leadership and job satisfaction for professionals in a nonprofit organization was fully mediated by self‐efficacy and trust (Yıldız & Şimşek, ). Given that transformational leadership encourages followers to go beyond expectations (Bycio et al, ), transformational leadership may enhance follower’s role breadth self‐efficacy and the confidence in being able to carry out a broader and more proactive role, beyond prescribed tasks (Parker, ), leading to proactive behavior.
H1: Role breadth self‐efficacy mediates the positive effect of transformational leadership on proactive behavior.
…”
Section: Transformational Leadership and Motivation To Proactivitymentioning
confidence: 93%
“…The implications of these findings have applicability across national settings and for effective management of nonprofit organizations internationally. Striving to find ways nonprofit leaders can increase employee job satisfaction and service quality is not likely to be limited to the United States (Bastida, Marimon, & Carreras, 2018; Choi, Goh, Adam, & Tan, 2016; Yıldız & Şimşek, 2016). The general model of leadership influencing performance outcomes, such as job satisfaction and service quality, through various mediating variables is supported in national and international contexts (Wipulanusat, Panuwatwanich, & Stewart, 2018; Yıldız & Şimşek, 2016) and in a variety of public and nonprofit sectors (Edú-Valsania, Moriano, & Molero, 2016; Wipulanusat et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Yıldız and Şimşek () showed transformational leadership's positive relation with satisfaction in a nonprofit sample and identified trust and self‐efficacy as mediators. Dwyer et al () showed a relation between transformational leadership and the job satisfaction of volunteers and identified the quality of the team relationships as a mediator.…”
Section: Theoretical Backgroundmentioning
confidence: 99%